Development of a User Interface for Traffic Light Control Using PLC at a Four-Way Intersection - Linda Sartika; Prasetia, Abdul Muis; Siti Nurholifah; Rahma Nur Amalia (Emitor: Jurnal Teknik Elektro, 2025)
In general, traffic light regulations (traffic tights) currently use fixed times where the lights are set to work alternately at fixed times, without paying attention to traffic flow conditions, for example at four intersections in each direction of the road the duration of the light is green, yellow, red at the same time. In this condition, there is a long queue on one side and a very short queue on the other, so setting the time duration equally will result in unnecessary stopping time. This research uses an experimental method which is carried out through the stages of procurement, assembling and carrying out trials. By using a Programmable Logic Controller (PLC) and User Interface (UI) to control and monitor the traffic light system at road intersections with the aim of designing and simulating the traffic light system at intersections manually using GX-Developer software and GT-software Designer3. PLC is used to automatically control the work of traffic lights which regulates the operational time of traffic lights which can respond and follow all commands given by the UI system. So testing the light timing settings at intersections can be set directly in the UI system with the timer in the traffic lights program, the timer from the calculation results, and the timer on the stopwatch having relative time differences. So, the real timer results were obtained on the stopwatch at the green light at intersection 1 for 41,79 seconds, the green light at intersection 2 for 41,79 seconds, the green light at intersection 3 for 25.77 seconds, and the green light at intersection 4 for 21,89 seconds. with yellow lights at all intersections 3 seconds, and red lights at all intersections only 1 second as the delay time between red and green lights at one intersection to another